Penggunaan Click-Wrap Agreement Pada E-Commerce: Tinjauan Terhadap Keabsahannya Sebagai Bentuk Perjanjian Elektronik - Martinelli, Imelda; Hadi Wibowo, Satria; Maheswari Andreas, Gertrud Felita; Ocarina Fae, Majolica (Jurnal Supremasi, 2024)
The development of e-commerce business highlights the rapid use of Click-Wrap Agreements alongside advances in information technology. However, debates over the validity of Click-Wrap Agreements as electronic contracts often arise. This research adopts a normative approach using secondary data. Electronic contracts are recognized by Indonesian law, as stipulated in Article 18 paragraph (1) of the ITE Law. Consequently, when consumers agree to Click-Wrap Agreements by clicking the 'click' button, both parties are bound and must adhere to the terms of the agreement under the law. Therefore, the regulation regarding the validity of Click-Wrap Agreements and their implications on the rights and obligations of e-commerce users need attention within the existing regulatory framework.